Has macroeconomic stability since 1992 been due to Keynesianism, monetarism or what? (2020)
On Wednesday 16 September 1992 (known at the time as ‘Black Wednesday’), heavy selling of the pound on the foreign exchanges forced it out of the European exchange rate mechanism (ERM). The UK’s exit from the ERM was regarded at the time as both a failure of economic policy and a national humiliation. As it is now 15 years later, the event can begin to be analysed from a wider historical perspective. The central point is surprising, but clear. The decade following the pound’s expulsion from the ERM was a triumph for British economic policy-making. The sterling crisis of September 1992 did not foreshadow increased instability, but instead was followed by greater macroeconomic stability than in any previous phase of the UK’s post-war history (and probably than ever before in British history). Black Wednesday became Golden Wednesday.